PERAN PENGELOLA POSDAYA AL-BAROKAH DALAM PENGEMBANGAN KEWIRAUSAHAAN MASYARAKAT DESA SEKARWANGI KECAMATAN RAWAMERTA KABUPATEN KARAWANG - Sadili, Dadan; Santika, Tika; Dewi, Ratna (IKIP Siliwangi Bandung, 2023)
The present study aims to unearth the contribution by Al-Barokah Family Empowerment Service (hereinafter Posdaya) organizers to the promotion of entrepreneurship in the communities and to explore supporting and inhibiting factors of Posdaya project implementation in boosting the entrepreneurial commitment of Sekarwangi Village, Rawamerta District, Karawang Regency. Employing qualitative case study methodology, the research used observation, interview, and documentation techniques to collect the data. Results reveal that the role of the community organizers in general was carried out effectively. This was reflected in Posdaya management of four areas including education, health, economy and environment where learning motivation, healthy living, entrepreneurship and productivity are enhanced. Findings also indicate that the high motivation of the community organizers and residents is the most influential factor supporting the development. While the lack of early childhood educational staff, the lack of educational supports, lack of building capacity; the lack of capital and unorganized administrative accounting; the lack of healthcare providers, and the lack of facilities and infrastructure are the major obstacles to the education, economic, and health empowerment.